Analysis on English Village of Parit Baru Management, Organization, and Environment - Asih - Rosida Hidayah; Sahrawi - Sahrawi; Maliqul - Hafis; Aunurrahman - Aunurrahman (Journal of English Language Teaching and Education (JELTE), 2023)
The purpose of this research was to find out how the management, organization and environment of English village in Parit Baru. This research use a qualitative approach with a descriptive design with interview and observation as the tools of data collection. The subject for this research interview were informants selected by the researcher, are the head of Parit Baru village, the head of the English Education Study Program IKIP PGRI Pontianak, one of tutors in Parit Baru village, and one of the student parent. The result showed that the management of the English Village in Parit Baru existed since 2020, but activities were hampered due to Covid in 2021 after that the next activities went well as before. The English Village in Parit Baru is administratively coordinated by the Head of the English Education Study Program, IKIP PGRI Pontianak. English Village activities are held at the Parit Baru Village Office.